Synthesis and Testing of New Kinetic Inhibitor of Methane Hydrates Based on Amphiphilic Polyurethane - Farkhadian A.; Varfolomeev M.; Zaripova Y.; Yarkovoi V. (2019)
© 2019, Springer Science+Business Media, LLC, part of Springer Nature. A kinetic inhibitor of methane hydrate formation was developed on the basis of amphiphilic polyurethane. The efficiency of the new reagent was evaluated in a high-pressure reactor with agitation by measuring the time for the beginning of hydrate formation and the change of pressure in the system. The results show the excellent inhibiting effect of amphiphilic polyurethane in increasing the induction time (by 15 times) and reducing the growth rate of hydrates (by 2.5 times) compared with a system with pure water In addition, the urethane-based inhibitor did not show significant growth of methane hydrates after nucleation.